The immunohistochemical evaluation of selected markers in the left atrium of dogs with end-stage dilated cardiomyopathy and myxomatous mitral valve disease – a preliminary study. Issue 1 (December 2016) - Janus, Izabela; Kandefer-Gola, Małgorzata; Ciaputa, Rafał; Noszczyk-Nowak, Agnieszka; Pasławska, Urszula; Tursi, Massimiliano; Nowak, Marcin
Abstract Background Dilated cardiomyopathy (DCM) and myxomatous mitral valve disease (MMVD) are the most common diseases noted in dogs. Although their pathogenesis varies, both include a significant enlargement of the left atrium. The study was carried out on left atrial specimens obtained from 56 dogs, including those from 34 dogs with clinically diagnosed MMVD, 15 dogs with DCM and 7 dogs without heart disease (control group). Dogs in the MMVD and the DCM groups presented with left atrial enlargement and stage D heart failure. The specimens underwent immunohistochemical examination using desmin, vimentin, periostin and caspase-3 antibodies. Results There were alterations in the expression of the studied proteins in the study groups compared to the control group. The changes included: irregularity of desmin cross-striation and desmosomes, a higher amount of vimentin-positive cells, a change in the periostin expression pattern from cytoplasmic to extracellular, and a lower expression of caspase-3. The alterations were more pronounced in the DCM group than in the MMVD group. Conclusions During heart failure, the pattern of desmin, vimentin, periostin and caspase-3 expression alters in the left atrium, regardless of the cause. The changes are more pronounced in dogs with DCM than in dogs with MMVD and similar left atrial enlargement, suggesting that volume overload may not be the only cause of myocardial changes in DCM.